Usefulness of Nasometer in Evaluating Velopharyngeal Function - SAIJO, Hideto; NARITA, Rika; TAKAHASHI, Michiko; HIRANO, Yukiko; UCHINO, Natsuko; KASHIWAGI, Miki; OHKUBO, Kazumi; TANIGUCHI, Asako; HOSHI, Kazuto (Journal of Japanese Cleft Palate Association, 2024)
The purpose of this study was to measure the nasalization rate (Nasalance score, NS) using a Nasometer, compare it with the judgment made by conventional speech therapists (ST), and evaluate the velopharyngeal closing function (VPC), to examine the usefulness of the Nasometer for evaluations. 　The subjects were 32 patients with cleft lip and palate. VPC was evaluated in four stages by an experienced ST, and the average and maximum values of NS (vowel [i], consonant [tsu], low-pressure sentences, and high-pressure sentences) were obtained. 　In addition, we calculated the correlation coefficient between the four-level ST evaluation and NS. Furthermore, the difference in mean values was tested using the Mann-Whitney U test. In addition, ROC analysis was performed on NS, and the cutoff value and AUC value were determined. 　As a result, VPC was determined by ST in 13 cases with good VPC, 5 cases with almost good, 10 cases with mild poor, and 4 cases with poor. Based on these results, good and almost good were classified into two good groups, and mild poor and poor were classified into two poor groups. For NS, there was a significant difference in the average value and maximum value of all stimulus sentences between the two good and two poor groups at p < 0.01, and there was also a positive correlation with the four-level evaluation by ST. In the ROC analysis, the AUC value was ‘tsu’ and the NS average and maximum values for high pressure sentences were 0.9 or higher. The cutoff values varied widely, with the average NS value for each stimulus sound and sentence ranging from 23 % to 53 %, and the maximum NS value from 62 % to 84 %. The cutoff value that separates the VPC of the two good groups and two poor groups from the AUC value is useful if it is ‘tsu’ for the average NS value, in the 20 % range for high pressure sentences, in the 60 % range for ‘tsu’ in the maximum NS value, and in the 80 % range for high pressure sentences. 　The nasometer test was considered to be a highly useful test for evaluating VPC. In addition, the cutoff values for each stimulus sound/sentence ranged from 23 % to 53 % for the average NS value and from 62 % to 84 % for the maximum NS value. 　The cutoff value that separates the good VPC group and the poor VPC group from the AUC value is in the 20 % range for ‘tsu’ and high pressure sentences in the NS average value, and in the 60 % range for ‘tsu’ and in the 80 % range for high pressure sentences in the NS maximum value. 　The nasometer is useful for assessing VPC in conjunction with auditory evaluations by an ST. 　However, this study did not control for age, gender, or disease severity, so the current NS values have limitations as reference values; we would like to address these issues in the future.